The Mediating Role of Organizational Agility on the Relationship between Environmental Uncertainty and Innovation in Hotels - أحمد، ياسر عبدالعاطي; دراز، هيثم مختار (جامعة مدينة السادات - كلية السياحة والفنادق, 2022)
تؤدي الرشاقة التنظيمية إلى العديد من النتائج الإيجابية للفنادق، مثل التكيف مع بيئة متقلبة وغير مؤكدة وديناميكية، وزيادة جودة المنتج أو الخدمة، إلخ. بالإضافة إلى ذلك، أصبحت الرشاقة التنظيمية ضرورية للابتكار بأنواعه المختلفة. ونظرا لأن الرشاقة أمر بالغ الأهمية بالنسبة للفنادق، فمن المهم جدا أن يكونوا على دراية بأثارها. وبالتالي، هدفت هذه الدراسة إلى تحديد درجة عدم اليقين البيئي (environmental uncertainty) في الفنادق وتقييم الرشاقة التنظيمية والابتكار في الفنادق؛ وقياس مدي تأثير عدم اليقين البيئي على أبعاد الابتكار المختلفة؛ وأخيرا دراسة تأثير الرشاقة كمتغير وسيط على العلاقة بين عدم اليقين البيئي والابتكار في الفنادق. ولتحقيق هذه الأهداف، اشتمل مجتمع الدراسة على مديري الأقسام والمشرفين في فنادق الخمس نجوم بالقاهرة الكبرى. وتم أخذ عينة ملائمة لتحقيق أهداف هذا البحث، حيث تم توزيع 480 استمارة استقصاء على العينة. وكانت الاستمارات الصالحة للتحليل 420، بمعدل استجابة 87.5 في المائة. ولتحليل هذه الاستمارات إحصائيا، تم استخدام التحليل الوصفي، وتحليل الارتباط، وتحليل الانحدار المتعدد. وأظهرت نتائج البحث أن عدم اليقين البيئي له تأثير إيجابي على الأبعاد الأربعة للابتكار الفندقي (أي ابتكار المنتجات، وابتكار العمليات، والابتكار التنظيمي، والابتكار التسويقي). بالإضافة إلى ذلك، بينت النتائج أن الرشاقة التنظيمية تتوسط بشكل كامل تأثير عدم اليقين البيئي على الأبعاد الأربعة للابتكار الفندقي. ومن ثم، فقد تمت التوصية بضرورة استمرار الفنادق في الممارسات الجيدة للرشاقة التنظيمية. Organizational agility leads to many positive outcomes for hotels, such as adapting to and surviving in a volatile, uncertain, and dynamic environment, increasing product or service quality, etc. In addition, agility has become essential for different types of innovation. As agility is of crucial importance for hotels, they must be aware of its effects. Thus, this study aimed at determining the degree of environmental uncertainty (EU) in hotels; assessing the agility and innovation in hotels; investigating how the EU influences innovation dimensions, and finally examining the effect of agility as a mediating variable on the relationship between EU and innovation in hotels. The research population was the department managers and supervisors in five-star hotels in Greater Cairo. The convenience sampling method was adopted to attain the objectives of this research. A total of 480 questionnaire forms were handed out to the respondents. The questionnaires valid for analysis were 420, with a response rate of 87.5 percent. To analyze these forms, descriptive analysis, correlation analysis, and multiple regression analysis were used. The main results revealed that the EU has a positive effect on the four dimensions of hotel innovation (i.e., product innovation, process innovation, organizational innovation, and marketing innovation). Additionally, the results showed that organizational agility fully mediates the impact of the EU on the four dimensions of hotel innovation. Hence, it was recommended that hotels should continue with the best practices of organizational agility.
Keywords: الالتزام التنظيمي -- التنظيم البيئي -- الابتكار التسويقي -- الخدمات الفندقية